Radio emission from outflow–cloud interaction and its constraint on tidal disruption event outflow. Issue 3 (23rd December 2021) - Mou, Guobin; Wang, Tinggui; Wang, Wei; Yang, Jingjing
ABSTRACT: Tidal disruption event (TDE) can launch an ultrafast outflow. If the black hole is surrounded by large amounts of clouds, outflow–cloud interaction will generate bow shocks, accelerate electrons, and produce radio emission. Here, we investigate the interaction between a non-relativistic outflow and clouds in active galaxies, which is manifested as outflow–BLR (broad-line region) interaction, and can be extended to outflow–torus interaction. This process can generate considerable radio emission, which may account for the radio flares appearing a few months later after TDE outbursts. Benefitting from efficient energy conversion from outflow to shocks and the strong magnetic field, outflow–cloud interaction may play a non-negligible, or even dominating role in generating radio flares in a cloudy circumnuclear environment if the CNM density is no more than 100 times the Sgr A*-like one. In this case, the evolution of radio spectra can be used to directly constrain the properties of outflows.